Chicken Anti-Campylobacter Vaccine – Comparison of Various Carriers and Routes of Immunization - Kobierecka, Patrycja A.; Wyszyńska, Agnieszka K.; Gubernator, Jerzy; Kuczkowski, Maciej; Wiśniewski, Oskar; Maruszewska, Marta; Wojtania, Anna; Derlatka, Katarzyna E.; Adamska, Iwona; Godlewska, Renata; Jagusztyn-Krynicka, Elżbieta K. (Frontiers in Microbiology, 2016)
Campylobacter spp, especially the species Campylobacter jejuni, are important human enteropathogens responsible for millions of cases of gastro-intestinal disease worldwide every year. C. jejuni is a zoonotic pathogen, and poultry meat that has been contaminated by microorganisms is recognized as a key source of human infections. Although numerous strategies have been developed and experimentally checked to generate chicken vaccines, the results have so far had limited success. In this study, we explored the potential use of non-live carriers of Campylobacter antigen to combat Campylobacter in poultry. First, we assessed the effectiveness of immunization with orally or subcutaneously delivered GEM (Gram-positive Enhancer Matrix) particles carrying two Campylobacter antigens: CjaA and CjaD. These two immunization routes using GEMs as the vector did not protect against Campylobacter colonization. Thus, we next assessed the efficacy of in ovo immunization using various delivery systems: GEM particles and liposomes. The hybrid protein CjaAD, which is CjaA presenting CjaD epitopes on its surface, was employed as a model antigen. We found that CjaAD administered in ovo at embryonic development day 18 by both delivery systems resulted in significant levels of protection after challenge with a heterologous Campylobacter jejuni strain. In practice, in ovo chicken vaccination is used by the poultry industry to protect birds against several viral diseases. Our work showed that this means of delivery is also efficacious with respect to commensal bacteria such as Campylobacter. In this study, we evaluated the protection after one dose of vaccine given in ovo. We speculate that the level of protection may be increased by a post-hatch booster of orally delivered antigens.